"I Ain't Even Gonna Cap to It": Ethnography‐as‐Surveillance and Dark Sousveillance in the Classroom. (28th March 2022) - Pannell, Justin Lance
Abstract : This article theorizes classroom ethnography in the socio‐historical context of the U.S. as a form of racialized surveillance which is calibrated by anti‐Black colonial discourses, racially saturated perception, and one's vulnerability to interpellation. Focusing on the interaction of "Dominic, " a Black focal student, which was documented through ethnographic fieldwork, I conduct a frame analysis to investigate how ethnographic surveillance, as a racialized technology of power, becomes relevant to the frames Dominic negotiated. The analysis demonstrates that a surveillance frame was consequential to Dominic's interaction and that Dominic's verbal behavior was sensitive to the racialized element of surveillance generally and to anti‐blackness specifically. The analysis further shows how Dominic engaged in "dark sousveillance" (Browne 2015) as a form of ethnographic refusal, and the ensuing discussion considers aspects of reflexive practice by which ethnographer‐surveillers in education may engage in "abolitionist" (Shange 2019) ethnography.